1986
DOI: 10.1042/bj2340373
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Ibβ is the only phosphorylated major membrane glycoprotein in human platelets

Abstract: Platelets were metabolically labelled with 32P and the phosphoproteins examined by two-dimensional non-reduced/reduced gel electrophoresis and isoelectric-focusing/gel electrophoresis. Comparison with similar separations of surface-labelled platelets showed that the only major glycoprotein which is phosphorylated is the beta-subunit of glycoprotein Ib, indicating that this subunit contains a cytoplasmic segment. The identification was confirmed using immunoblotting with an antibody to the beta-subunit. Phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Kalomiris et al [23] reported that GPIbfl is a transmembrane protein with a reactive endofacial sulfhydryl group. Wyler et al [22] showed that the / 3 subunit of GPIb contains a phosphorylation site. While GPIbp and GP17 are similar in their molecular mass and are labeled similarly with carbohydrate-specific labeling methods, we were able to demonstrate that polyclonal rabbit antibodies against these two glycoproteins do not cross-react.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kalomiris et al [23] reported that GPIbfl is a transmembrane protein with a reactive endofacial sulfhydryl group. Wyler et al [22] showed that the / 3 subunit of GPIb contains a phosphorylation site. While GPIbp and GP17 are similar in their molecular mass and are labeled similarly with carbohydrate-specific labeling methods, we were able to demonstrate that polyclonal rabbit antibodies against these two glycoproteins do not cross-react.…”
Section: Discussionmentioning
confidence: 99%
“…Fox et al [20] and Okita et al [21] reported that GPIb is linked via actin-binding protein to the cytoskeleton in resting platelets. Wyler et al [22] have shown that the GPIbg subunit is phosphorylated; Kalomiris et al [23] reported labeling of the p subunit by membrane-permeable fluorescent reagents which bind to reactive thiol groups. Methods for the purification of intact GPIb have only recently been established and much remains to be discovered about its structure.…”
Section: Studies Performed By Solum Et Al [I81 and Coller Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In nonactivated platelets, GPIb is complexed to actin-binding protein and thereby to the cytoskeleton, via the intracytoplasmic segment of the alpha chain (3). The role of GPIb3 is unknown, although it is the major platelet membrane protein to be phosphorylated when resting platelets are incubated with [32P]phosphate (4). This phosphorylation, thought to occur at Serl66 in the mature platelet protein, is present under conditions that increase intracellular cAMP and may contribute to the inhibitory actions of cAMP by inhibiting collagen-induced polymerization of actin (5).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, phosphorylation of platelet membrane proteins has been studied (30,36). The only serine/threonine-phosphorylated major membrane glycoprotein identified was GPIb␤ (30). GPIb␤ is phosphorylated at Thr 166 when platelets are stimulated with agents that enhance intracellular cAMP level (36,37).…”
Section: Discussionmentioning
confidence: 99%